A photocatalyst and preparation method thereof

By introducing nitrogen-doped carbon nanotubes on CuFe2O4, a CuFe2O4@N-CNTs composite catalyst was formed, and combined with photocatalytic-Fenton technology, the existing photocatalysts have been solved, and efficient photocatalytic performance has been achieved.

CN119771462APending Publication Date: 2025-04-08河北工业职业技术大学
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411817530.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The existing semiconductor photocatalysts have disadvantages such as low utilization of visible light and fast recombination of photogenerated electrons to positive holes, resulting in low catalytic efficiency.

Method used

By introducing nitrogen-doped carbon nanotubes (N-CNTs), the tiny CuFe2O4 particles are uniformly supported on the surface of the carbon nanotube to form a CuFe2O4@N-CNTs composite catalyst, and a combination of photocatalytic-Fenton dual system is used.

Benefits of technology

The utilization rate of photocatalysts for light energy is improved, the adsorption capacity of pollutants is enhanced, the easy recombination problem between photogenerated electrons and positive pore pairs is solved, and the photocatalytic activity is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119771462A_ABST
    Figure CN119771462A_ABST
Patent Text Reader

Abstract

The invention discloses a photocatalyst and a preparation method thereof, belonging to the field of photocatalysts, and the preparation method comprises the steps: S1: weighing copper nitrate trihydrate and iron nitrate nonahydrate, dissolving them in deionized water to obtain solution A, weighing citric acid and adding them to deionized water to dissolve them; S2: weighing nitrogen-doped carbon nanotubes and adding them to solution A prepared by S1 and stirring them to obtain mixed solution B; S3: under stirring, adding the citric acid complexing agent solution prepared by S1 to the mixed solution B prepared by step S2, stirring to form a viscous colloidal solution; S4: putting the colloidal solution in S3 into an oven for complexing reaction to form a dry gel, then grinding and crushing, and putting it into a muffle furnace for calcination to obtain a CuFe2O4@N‑CNTs composite catalyst, i.e. a photocatalyst. The photocatalyst prepared by the present invention increases the light absorption capacity of pollutants, and at the same time solves the problems of low absorption of visible light and insufficient catalytic activity of photocatalytic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photocatalysts, and in particular relates to a photocatalyst and a preparation method thereof. Background Art

[0002] In environmental ecological pollution, water pollution caused by the widespread use and abuse of organic substances such as antibiotics has attracted great attention from the society.

[0003] Antibiotics have good bactericidal and antibacterial effects. There are many types of antibiotics, which are widely used in medical, aquaculture, industry and agriculture. Since humans or animals and plants cannot fully absorb the antibiotics they use, a large amount of these drugs and their metabolites are continuously discharged into the environment, causing damage to the ecosystem. For example, they have toxic effects on aquatic organisms, directly affecting their growth and reproduction; they damage the living conditions of microorganisms in the soil, thereby disrupting the balance of the soil ecosystem; in addition, the excessive abuse of antibiotic pollution will also cause medical drug resistance problems, making bacteria that are originally sensitive to antibiotics become resistant, affecting the treatment effect of bacterial infections, etc. And sewage treatment plants cannot completely degrade them. Therefore, antibiotic pollution poses a huge risk to human, animal and plant health. In response to this problem, it is urgent to study and develop innovative, efficient and green methods for removing antibiotics such as tetracycline. The light-Fenton synergistic advanced oxidation technology, which combines photocatalysis and Fenton oxidation technology and involves semiconductor photocatalytic materials, has the advantages of high efficiency, low energy consumption, no secondary pollution, and simple operation. It is a green and environmentally friendly technology that conforms to the current national "dual carbon" concept.

[0004] However, most semiconductor photocatalysts have low visible light utilization efficiency and low photogenerated - -h + In recent years, in order to obtain better photocatalytic active materials, the ferrite bimetallic catalyst CuFe2O4 with stable structure and excellent properties has attracted more and more attention, but it also has the disadvantages of photogenerated - -h + Defects such as easy compounding and easy agglomeration of monomer particles affect the photocatalytic activity. Summary of the invention

[0005] 1. Technical issues to be resolved

[0006] In view of the deficiencies in the prior art, the present invention provides a photocatalyst and a preparation method thereof, which solve the problems raised in the above background technology.

[0007] (II) Technical solution

[0008] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0009] A method for preparing a photocatalyst comprises the following steps:

[0010] S1: Weigh 0.296g of copper nitrate trihydrate and 0.808g of ferric nitrate nonahydrate, dissolve them in 50ml of deionized water to obtain solution A; weigh 6.3g of citric acid and add it to 100ml of deionized water, stir magnetically and heat in a water bath to 80℃ to dissolve it, to obtain a citric acid complexing agent solution with a concentration of 0.3mol / L;

[0011] S2: Weigh 0.08 g of nitrogen-doped carbon nanotubes and add them to the solution A prepared in step S1 and stir to obtain a mixed solution B;

[0012] S3: under stirring, adding the citric acid complexing agent solution prepared in step S1 to the mixed solution B prepared in step S2, heating in a water bath at 80° C. and stirring for 4 to 5 hours until a viscous colloidal solution is formed;

[0013] S4: The colloidal solution in S3 is placed in an oven at 130°C for 12 hours for complexation reaction to form a dry gel, and then the dry gel is ground into powder using a mortar and calcined in a muffle furnace to obtain a CuFe2O4@N-CNTs composite catalyst, which is a photocatalyst.

[0014] The method for preparing nitrogen-doped carbon nanotubes (N-CNTs) comprises the following steps:

[0015] Q1: Weigh 1g of melamine and carbon nanotubes, dissolve in a mixed solution of 40ml methanol and 80ml pure water, stir under ultrasonic for 30min until completely dissolved to obtain solution C, stir in a water bath at 80℃ until solution C becomes thick, freeze in a refrigerator for 1-2h, and then freeze-dry under vacuum for 12h to obtain a precursor;

[0016] Q2: The precursor prepared in Q1 is placed in a tube furnace and nitrogen is introduced, and calcined in a nitrogen atmosphere to obtain nitrogen-doped carbon nanotubes (N-CNTs).

[0017] Furthermore, the mass ratio of melamine to carbon nanotubes is 1:1.

[0018] Further, the temperature was raised to 700°C and calcined for 1 h.

[0019] Furthermore, the heating rate in step Q1 is 5°C / min.

[0020] Furthermore, in step S4, the specific operation of the calcination treatment is: calcination at 850° C. for 2 hours.

[0021] A photocatalyst is prepared by adopting the method.

[0022] After adopting the above technical solution, the present invention has the following beneficial effects compared with the prior art:

[0023] 1. CuFe2O4 has a cubic spinel structure and a narrow bandgap, which makes it have high chemical stability, good visible light response and photocatalytic activity. It also has excellent electrical conductivity and effective thermal performance. CNTs, as a new type of nanomaterial, has large π bonds on its surface, good electrical properties and a large specific surface area, and has its own photoluminescence effect.

[0024] The present invention introduces N atoms to form a defect structure on the surface of CNTs, so that CuFe2O4 tiny particles can be evenly loaded on the surface of carbon nanotubes, which is conducive to the uniform dispersion of CuFe2O4, solves the problem of particle agglomeration, and improves the light absorption capacity of CuFe2O4. The carbon nanotubes themselves absorb visible light and the tubular structure increases multiple reflections of light, further improving the utilization rate of light energy by the photocatalyst, thereby greatly improving the adsorption capacity of the photocatalyst to pollutants.

[0025] 2. The present invention utilizes the good charge conduction performance of CNTs to achieve e - Rapid transfer of CuFe2O4 materials to solve the problem of photogenerated - With h + The problem of easy recombination is solved by using the technology combining photocatalysis and Fenton dual system to realize photogenerated - With h + Maximum separation can solve the problem of low absorption of visible light and insufficient catalytic activity of current photocatalytic materials from a deep level.

[0026] 3. The present invention selects the carbon-based material of N-doped CNTs as a carrier, loads and modifies CuFe2O4, and forms a composite material with excellent photocatalytic performance. The surface of the prepared CuFe2O4@N-CNTs composite material is relatively rough, which increases the contact area between the catalyst and the target substrate in the polluted water to a certain extent, and is more conducive to the degradation of the substrate, thereby achieving the purpose of removing pollutants in the water. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Attached Figure 1 Solid UV-visible diffuse reflectance spectra of CFO, CFO@C and CFO@NC prepared in the examples and comparative examples.

[0028] Attached Figure 2 KM conversion curves corresponding to the solid UV-visible diffuse reflectance spectra of CFO, CFO@C and CFO@NC prepared in the examples and comparative examples.

[0029] Attached Figure 3PL spectra of CFO, CFO@C and CFO@NC prepared in the examples and comparative examples.

[0030] Attached Figure 4 The graph shows the degradation results of tetracycline hydrochloride by CFO, CFO@C and CFO@NC prepared in the examples and comparative examples.

[0031] Attached Figure 5 This is the activity curve of the tetracycline hydrochloride cyclic degradation experiment of CFO@NC prepared in Example 1.

[0032] Attached Figure 6 This is a comparison chart of the degradation efficiency of the tetracycline hydrochloride cyclic degradation experiment of CFO@NC prepared in Example 1.

[0033] Attached Figure 7 This is a diagram showing the universal experimental performance of CFO@NC prepared in Example 1.

[0034] Attached Figure 8 This is the microscopic morphology of CFO@NC prepared in Example 1. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] The method for preparing nitrogen-doped carbon nanotubes (N-CNTs) comprises the following steps:

[0038] Q1: Weigh 0.5g melamine and 0.5g carbon nanotubes, dissolve in a mixed solution of 40ml methanol and 80ml pure water, stir for 30min under ultrasonication until completely dissolved to obtain solution C, stir in a water bath at 80℃ until solution C becomes thick, place in a refrigerator and freeze for 1-2h, then freeze-dry under vacuum for 12h to obtain a precursor;

[0039] Q2: The nitrogen-doped carbon nanotube precursor prepared in Q1 was placed in a tubular furnace and nitrogen was introduced to increase the temperature to 700°C at a heating rate of 5°C / min, and calcined for 1 hour to obtain nitrogen-doped carbon nanotubes (N-CNTs).

[0040] A method for preparing a photocatalyst comprises the following steps:

[0041] S1: Weigh 0.808g of copper nitrate trihydrate and 0.296g of ferric nitrate nonahydrate, dissolve them in 50ml of deionized water to obtain solution A, weigh 6.3g of citric acid and add them to 100ml of deionized water, stir magnetically and heat in a water bath to 80°C to dissolve them, to obtain a citric acid complexing agent solution with a concentration of 0.3mol / L;

[0042] S2: Weigh 0.08 g of nitrogen-doped carbon nanotubes and add them to the solution A prepared in step S1 and stir to obtain a mixed solution B;

[0043] S3: under stirring, add the citric acid complexing agent solution prepared in S1 to the mixed solution B prepared in step S2, heat in a water bath at 80°C and stir for 4 hours until a viscous colloidal solution is formed;

[0044] S4: The colloidal solution in S3 is placed in an oven at 130°C for 12 hours for complexation reaction to form a dry gel, and then the dry gel is ground into powder using a mortar, and placed in a muffle furnace for calcination at 850°C for 2 hours to obtain a CuFe2O4@N-CNTs composite catalyst (hereinafter referred to as CFO@NC). The CuFe2O4@N-CNTs composite catalyst is a composite catalyst material with excellent photocatalytic performance.

[0045] Comparative Example 1

[0046] Different from Example 1, no nitrogen-doped carbon nanotubes are added during the preparation of the photocatalyst.

[0047] A method for preparing a photocatalyst comprises the following steps:

[0048] S1: Weigh 0.808g of copper nitrate trihydrate and 0.296g of ferric nitrate nonahydrate, dissolve them in 50ml of deionized water to obtain solution A, weigh 6.3g of citric acid and add them to 100ml of deionized water, stir magnetically and heat in a water bath to 80°C to dissolve them, to obtain a citric acid complexing agent solution with a concentration of 0.3mol / L;

[0049] S2: under stirring, adding the citric acid complexing agent solution prepared in step S1 to the mixed solution B prepared in step S1, heating in a water bath at 80° C. and stirring for 4 h until a viscous colloidal solution is formed;

[0050] S3: The colloidal solution in S2 is placed in an oven at 130°C for 12 hours for complexation reaction to form a dry gel, and then the dry gel is ground into powder using a mortar, and placed in a muffle furnace for calcination at 850°C for 2 hours to obtain a CuFe2O4 catalyst (hereinafter referred to as CFO).

[0051] Comparative Example 2

[0052] Different from Example 1, during the preparation of the photocatalyst, the nitrogen-doped carbon nanotubes are replaced with hydroxylated multi-walled carbon nanotubes (CNTs).

[0053] The hydroxylated multi-walled carbon nanotubes were purchased from China Science Times Nanomaterials Co., Ltd.

[0054] A method for preparing a photocatalyst comprises the following steps:

[0055] S1: Weigh 0.808g of copper nitrate trihydrate and 0.296g of ferric nitrate nonahydrate, dissolve them in 50ml of deionized water to obtain solution A, weigh 6.3g of citric acid and add it to 100ml of deionized water, stir magnetically and heat in a water bath to 80°C to dissolve it to obtain a citric acid complexing agent solution with a concentration of 0.3mol / L;

[0056] S2: Weigh 0.08 g of carbon nanotubes and add them to the solution A prepared in step S1 and stir evenly to obtain a mixed solution B;

[0057] S4: under stirring, add the citric acid complexing agent solution prepared in S1 to the mixed solution B prepared in step S2, heat in a water bath at 80° C. and stir for 4 h until a viscous colloidal solution is formed;

[0058] S4: The colloidal solution in S3 was placed in an oven at 130°C for 12 hours for complexation reaction to form a dry gel, and then the dry gel was ground into powder using a mortar, and placed in a muffle furnace for calcination at 850°C for 2 hours to obtain a CuFe2O4@CNTs catalyst (hereinafter referred to as CFO@C).

[0059] Result analysis experiment:

[0060] 1. Solid UV-Vis Diffuse Reflectance (UV-Vis DRS).

[0061] UV-Vis DRS was used to perform spectral scanning on CFO@CN, CFO and CFO@C prepared in Example 1, Comparative Example 1 and Comparative Example 2. The results are as follows: Figure 1 As shown, UV-Vis DRS can determine the light utilization capabilities of CFO@CN, CFO, and CFO@C.

[0062] The Eg values ​​of the three samples were determined according to the Kubelka-Munk theory, and the calculation method is (αhv) n =A(hv-Eg), where α is the absorption coefficient, hv is the photon energy, A is the absorption coefficient of the sample at the edge of the absorption band, and Eg is the band gap width. Since CuFe2O4 is an indirect semiconductor, n is taken as 1 / 2. The calculated band gaps of CFO, CFO@C and CFO@NC are 1.43eV, 0.91eV and 0.85eV, respectively. Figure 2shown.

[0063] From the solid ultraviolet-visible diffuse reflectance (UV-Vis DRS) experiment and results, we can know that Figure 1 CFO, CFO@C and CFO@NC all have a wide absorption range for light, among which the absorption band edge of CFO is around 875nm, while the absorption wavelengths of CFO@CN and CFO@C samples have undergone a significant red shift, expanding the absorption range of light. At the same time, the absorption wavelength of CFO@CN samples is also shifted upward compared to that of CFO@C, indicating that N doping improves the light energy utilization rate of CFO@CN. The band gaps of CFO, CFO@C and CFO@NC are 1.43eV, 0.91eV and 0.85eV respectively. It can be seen that CFO@CN has the narrowest bandgap, which once again proves that N doping can improve the light energy utilization rate of CFO@CN.

[0064] 2. Photoluminescence spectrum PL

[0065] Photoluminescence (PL) refers to the emission of light when a substance absorbs light energy of a specific wavelength. - is excited to an excited state, forming e - -h + Yes, then the electron returns to the ground state and recombine with the hole to emit fluorescence to form a spectrum. Therefore, the change of fluorescence intensity in the PL spectrum can well reflect the electron emission in the semiconductor photocatalyst. - -h + The lower the fluorescence intensity, the higher the separation and recombination efficiency of the photocatalytic material. - -h + The lower the recombination rate of the pair.

[0066] The PL spectra of CFO, CFO@C and CFO@NC prepared by the present invention at an excitation wavelength of 254 nm at 350-480 nm are as follows: Figure 3 shown.

[0067] In the above photoluminescence spectra PL results, the fluorescence peaks of CFO, CFO@C and CFO@NC samples appear at 350-400nm, and the fluorescence intensities of CFO@C and CFO@NC are significantly weaker than that of CFO, among which the fluorescence intensity of CFO@NC is the weakest. - -h + The recombination rate of the photocatalyst was the lowest and the photocatalytic performance was the highest, indicating that the doping of N and CNTs synergistically improved the catalytic performance of the prepared photocatalyst. This is because carbon nanotubes, as carriers, are the most photocatalytically active - The separation and migration of photogenerated - The separation efficiency of- -h + The photocatalytic performance of CNTs was improved by the addition of N. At the same time, the electron cloud density around the C atoms in CNTs was changed, which enhanced the e - conductivity, further preventing the catalyst from - -h + The photocatalytic performance is further improved.

[0068] 4. Photocatalytic activity test of CFO, CFO@C and CFO@NC prepared by the present invention.

[0069] Taking CFO, CFO@C and CFO@NC with the same molar mass, the degradation experiment of the same amount of tetracycline hydrochloride (TC) was carried out under the same visible light conditions in the single photocatalytic system, Vis / H2O2 system and light-Fenton synergistic system. The results are as follows Figure 4 shown.

[0070] It can be seen from the figure that TC is relatively stable under visible light irradiation at room temperature and pressure, with basically no change, and the influence of its own degradation can be ruled out. In the absence of photocatalysts, the degradation capacity of the Vis / H2O2 system for TC is also very limited. After 30 minutes of adsorption reaction under dark conditions, each group reached adsorption equilibrium, among which CFO and CFO@C had higher adsorption capacity for TC than CFO, indicating that the addition of carbon nanotubes improved the adsorption performance of organic pollutants.

[0071] Under the condition of 120min photocatalytic single system, the degradation rates of TC by CFO@C and CFO@NC reached 42.27% and 52.54%, respectively. Compared with CFO material, the degradation rate was only 22.16% under the same conditions. This shows that the addition of CNTs has an improved effect on the photocatalytic activity of CFO. This is because CNTs as carriers make CFO evenly distributed, inhibiting the aggregation of its particles, and the good conductivity of CNTs can promote e - The transfer of - The separation efficiency is greatly improved, thereby greatly improving its photocatalytic performance.

[0072] The degradation efficiencies of CFO, CFO@C and CFO@NC in the light-Fenton synergistic system were 75.8%, 92.19% and 94.11%, respectively, which were all greater than the catalytic efficiencies of CFO, CFO@C and CFO@NC in the single photocatalytic system and Vis / H2O2 system, and CFO@NC had the best catalytic efficiency.

[0073] This shows that the combination of photocatalysis and Fenton oxidation technology can improve the catalytic efficiency of CFO, CFO@C and CFO@NC. This is because the combination of photocatalysis and Fenton oxidation technology promotes the decomposition of H2O2 to produce ·OH, increases the concentration of ·OH in the solution, and enhances the Fenton oxidation performance; at the same time, the photo-Fenton synergistic effect accelerates the 2+ / Cu + and Fe 3+ / Fe 2+ The conversion between ion pairs and effectively inhibit the photogenerated - The compound improves the overall degradation efficiency of the reaction system.

[0074] In the photo-Fenton synergistic system, the catalytic efficiency of CFO@C is lower than that of CFO@NC. Combined with the catalytic efficiency of CFO in the photo-Fenton synergistic system, it can be seen that the combination of N and CNT synergistically improves the catalytic efficiency of CFO@NC.

[0075] Finally, it was concluded that the CFO@NC composite material had the best degradation effect in the photo-Fenton synergistic system. This was because the introduction of the non-metallic dopant N formed a defect structure on the surface of CNTs, overcoming its inertness caused by its overly regular structure, thereby generating more active sites to improve the efficiency of pollutant degradation; at the same time, this defect structure was more conducive to the uniform compounding of CFO on the surface of CNTs; in addition, the doping of N in CNTs induced the directional enrichment of pollutants around the catalytic material, reducing the migration distance of active free radicals and improving their utilization.

[0076] 5. Stability analysis of CuFe2O4@N-CNTs

[0077] 5.1 Cycle Experiment

[0078] Reusability and stability are important indicators for evaluating the performance of photocatalysts in actual sewage treatment.

[0079] The CFO@NC prepared in Example 1 was used to perform a cyclic degradation experiment of TC. After each cycle was completed, the used CFO@NC was added back to the original system by centrifugal separation, and TC and pure water were added to the solution to adjust the TC concentration back to 100 ppm after 30 minutes of dark reaction adsorption equilibrium. The degradation was repeated four times under the same conditions, each time for 120 minutes under photo-Fenton conditions. The experimental results are shown in FIG. Figure 5 and Figure 6 shown.

[0080] After four cycles of degradation of tetracycline hydrochloride organic pollutants, the degradation efficiency of CFO@NC can still be maintained at 87.09% (the four degradation rates are 94.06%, 93.35%, 90.86%, and 87.09% respectively). The results show that CFO@NC has high photocatalytic activity and can meet the requirements of multiple cycles.

[0081] 5.2 Universal Experiment

[0082] In practical applications, photocatalytic materials must not only have good catalytic activity and cyclic stability, but also be applicable to the degradation of a wide range of pollutants. Therefore, this experiment further explored the universal performance of CFO@NC composite materials by replacing different target substrates.

[0083] The CFO@NC prepared in Example 1 was used to perform degradation experiments on methylene blue (MB), rhodamine B (RHB), phenol (Phenol) and bisphenol A (BPA) of equal mass under 120 min photocatalysis and Fenton dual system. The results are as follows: Figure 7 As shown,

[0084] Figure 7 The degradation efficiencies of CFO@NC prepared in Example 1 for methylene blue (MB), rhodamine B (RHB), phenol (Phenol) and bisphenol A (BPA) were 98.24%, 93.57%, 84.95% and 88.69%, respectively, which indicates that CFO@NC has good catalytic activity for a variety of organic pollutants and can meet the requirements for treating wastewater with more complex components in real life.

[0085] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a photocatalyst, characterized in that: The following steps are involved: S1: Weigh 0.296 g of copper nitrate trihydrate and 0.808 g of ferric nitrate nonahydrate, dissolve them in 50 ml of deionized water to obtain solution A; weigh 6.3 g of citric acid, add it to 100 ml of deionized water, stir it with a magnetic stirrer and heat it in a water bath to 80°C to dissolve it, and obtain a citric acid complexing agent solution with a concentration of 0.3 mol / L; S2: Weigh 0.08 g of nitrogen-doped carbon nanotubes and add them to the solution A prepared in step S1, stir evenly, and obtain a mixed solution B; S3: under stirring, adding the citric acid complexing agent solution prepared in step S1 to the mixed solution B prepared in step S2, heating in a water bath at 80° C. and stirring for 4-5 hours to form a viscous colloidal solution; S4: The colloidal solution in S3 is placed in an oven at 130°C for 12 hours for complexation reaction to form a dry gel, and then the dry gel is ground into powder using a mortar and calcined in a muffle furnace to obtain a CuFe2O4@N-CNTs composite catalyst, which is a photocatalyst.

2. The method for preparing a photocatalyst according to claim 1, characterized in that: The method for preparing nitrogen-doped carbon nanotubes, The following steps are involved: Q1: Weigh 1g of melamine and carbon nanotubes, dissolve in a mixed solution of 40ml methanol and 80ml pure water, stir under ultrasonic for 30min until completely dissolved to obtain solution C, stir in a water bath at 80℃ until solution C becomes thick, freeze in a refrigerator for 1-2h, and freeze-dry under vacuum for 12h to obtain a precursor; Q2: The precursor prepared in Q1 is placed into a tubular furnace and nitrogen is introduced, and calcined in a nitrogen atmosphere to obtain nitrogen-doped carbon nanotubes.

3. The method for preparing a photocatalyst according to claim 2, characterized in that: The mass ratio of the melamine to the carbon nanotubes is 1:

1.

4. The method for preparing a photocatalyst according to claim 2, characterized in that: In step Q2, the specific operation of the calcination treatment is: heating to 700° C. and calcining for 1 hour.

5. The method for preparing a photocatalyst according to claim 4, characterized in that: The heating rate is 5°C / min.

6. The method for preparing a photocatalyst according to claim 1, characterized in that: In step S4, the specific operation of the calcination treatment is: calcination at 850° C. for 2 hours.

7. A photocatalyst, characterized in that: The method is prepared according to any one of claims 1 to 6.

Citation Information

Cited By

  • A method for preparing a composite visible light catalyst from a zinc extraction tailing of a steelmaking furnace dust oxygen pressure sulfuric acid

    CN120662310B